Non‐alcoholic fatty liver disease contributes to hepatocarcinogenesis in non‐cirrhotic liver: A clinical and pathological study. Issue 5 (25th April 2013) - Alexander, Jacob; Torbenson, Michael; Wu, Tsung‐Teh; Yeh, Matthew M.
Abstract Background and Aim Hepatocellular carcinoma (HCC) is a major complication of cirrhosis and has been increasing in incidence in recent years. Fatty liver disease is an increasingly common cause of chronic liver disease, and there have been several case reports of HCC in patients with non‐cirrhotic fatty liver disease. However, there is limited data from systematic studies with histological confirmation of the presence of both the HCC and the non‐cirrhotic fatty liver disease. Methods We studied the occurrence of fatty liver disease and the associated demographic, clinical, and pathological characteristics of a large cohort of patients with HCC in non‐cirrhotic livers. Patients with intrahepatic cholangiocarcinoma (CC) occurring in non‐cirrhotic livers and diagnosed during the same time period were used as the comparison group. Results Significant steatosis in the nontumor liver had a statistically significant association with HCC, being present in 54% (85/157) of HCC compared with 27% (32/120) of CC (P < 0.0001). Steatohepatitis was present in 15% (24/157) of HCC and 1% (2/120) of CC (P = 0.0014). Furthermore, HCC was more prevalent in cases with higher grades of steatosis. In addition, the recently described intratumoral steatohepatitic morphology of HCC (SH‐HCC) was also associated with significant steatosis in nontumor liver, with significant steatosis being present in 89% with SH‐HCC compared with 50% without SH‐HCC (P = 0.0162). Finally, SH‐HCC was increasingly more prevalent in patients with higher grades of nontumor steatosis. Conclusions Taken together, these findings suggest a strong association between fatty liver disease and HCC in non‐cirrhotic livers.